Exploring Engineering instructors' views about writing and online tools to support communication in Engineering. (2nd November 2017) - Howard, Sarah K.; Khosronejad, Maryam; Calvo, Rafael A.
ABSTRACT: To be fully prepared for the professional workplace, Engineering students need to be able to effectively communicate. However, there has been a growing concern in the field about students' preparedness for this aspect of their future work. It is argued that online writing tools, to engage numbers of students in the writing process, can support feedback on and development of writing in engineering on a larger scale. Through interviews and questionnaires, this study explores engineering academics' perceptions of writing to better understand how online writing tools may be integrated into their teaching. Results suggest that writing is viewed positively in the discipline, but it is not believed to be essential to success in engineering. Online writing tools were believed to support a larger number of students, but low knowledge of the tools limited academics' understanding of their usefulness in teaching and learning. Implications for innovation in undergraduate teaching are discussed.